The best Australian science writing 2014 - Hay, Ashley, 1971- (NewSouth Publishing, 2014)
Now in its fourth year, this popular and acclaimed anthology steps inside the Australia's finest scientific and literary minds to present a collection that celebrates the nation's finest science writing of the year. Featuring prominent authors - such as Tim Flannery, Jo Chandler, Frank Bowden and Iain McCalman, as well as many new voices - this annual anthology covers topics as diverse and wondrous as our "lumpy" universe, the creation of dragons, why are Sydney's golden orb weaver spiders getting fatter and fitter, and the frontiers of climate science